Ecological Fiscal Transfers and Regional Environmental Performance: The Moderating Role of Economic Growth - Nadia Triana Safitri; Novi Dirgantari; Sri Wahyuni; Edi Joko Setyadi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the influence of Ecological Fiscal Transfers (EFT) and economic growth on regional environmental performance in Indonesia. Persistent environmental degradation—including deforestation, water pollution, and low Environmental Quality Index (EQI) scores—suggests a gap between ecological fiscal policy design and realised outcomes. Adopting a quantitative approach, the study uses secondary data from 32 local governments receiving EFT during 2021–2023. Multiple linear regression and moderation analysis are employed to assess the effects of EFT, economic growth, and their interaction on environmental performance. The results indicate that neither EFT nor economic growth has a statistically significant effect on environmental performance, and economic growth does not exhibit a moderating role. These findings underscore the limited effectiveness of current EFT implementation, which appears constrained by coordination challenges, budgetary inefficiencies, and institutional capacity. The study recommends strengthening inter-agency coordination and adopting performance-based evaluation mechanisms to support the design and implementation of more effective ecological fiscal policies.